STUDI KOMPARASI MOTIVASI DAN HASIL BELAJAR SISWA PONDOK PESANTREN DENGAN SISWA LUAR PONDOK PESANTREN - Moch. Fauzi (Almeera Education, 2024)
This research aims to determine the differences in motivation and mathematics learning outcomes of Roudlotul Ulum Randuagung Islamic Middle School students who live in Islamic boarding schools and outside Islamic boarding schools. This research is a type of comparative research with a quantitative approach. The variables in this research consist of: learning motivation of students living in Islamic boarding schools (X1.1), learning motivation of students living outside Islamic boarding schools (X1.2), learning outcomes of students living in Islamic boarding schools (X2.1), learning outcomes of students living outside Islamic boarding schools (X2.2). The population in this study were all students at Roudlotul Ulum Randuagung Islamic Middle School, totaling 68 students. This research uses a comparative quantitative approach and uses normality and homogeneity test statistics. Based on the research results obtained, the results of calculations using the Independent Sample t-test with SPSS 25 on student learning motivation produced a Sig 2 Tailed value of 0.142 > 0.05, meaning that there is no difference in the learning motivation of students who live in Islamic boarding schools and students who live in Islamic boarding schools. House. Meanwhile, the results of calculations using the Independent Sample t-test with SPSS 25 on student learning outcomes produced a Sig 2 Tailed value of 0.908 > 0.05, meaning there is no difference in the learning outcomes of students who live in Islamic boarding schools and students who live at home.